A riparian plant community from the upper Maastrichtian of the Pyrenees (Catalonia, NE Spain). (September 2015) - Marmi, Josep; Martín-Closas, Carles; Fernández-Marrón, Mª Teresa; Fondevilla, Víctor; Gomez, Bernard
Abstract: Angiosperms began to colonise riparian habitats very soon in their evolutionary history, probably already in the Aptian, but it is still poorly known when flowering plants finally dominated entirely these kind of communities as they do in the present. A new fossil plant locality (Molí del Baró-1) from the upper Maastrichtian of the Southern Pyrenees is described in which meandering river facies represent one of the first riparian communities formed only by angiosperms. The fossil assemblage consists of abundant leaves, seeds, logs and sporomorphs. Angiosperms remains dominate in all these cases and the leaf sample is mostly composed of a new eudicot willow-like species, Saliciphyllum gaetei sp. nov., the palm Sabalites longirhachis and an helophytic monocot. Pollen remains suggest that the later belonged to Typhaceae. Most of these plant remains were parautochthonous and deposited in a pond formed in the accretional part of a meander loop. The locality of Molí del Baró-1 represents an unique plant fossil assemblage in the uppermost Cretaceous of southern Europe. It clearly differs from those reported in other Maastrichtian localities of the Pyrenees (Fumanya and South Isona) and from the Campanian-Maastrichtian of Austria and Romania. In addition, it reflects a surprisingly modern physiognomy for a Late Cretaceous riverine plant assemblage that was built up with willow-like plants, palms and reeds. Highlights: A new plant community from the upper Maastrichtian Iberian Peninsula is reconstructed. The plant community was composed of a new eudicot willow-like species, palms and a likely member of Typhaceae. These plants represent one of the first riparian communities formed only by angiosperms. The Molí del Baró-1 represents an unique plant fossil assemblage in the uppermost Cretaceous of southern Europe.